Online learning platforms in Bangladesh: A comparative study on Bangladeshi MOOC-based learning institutes (LIS TODAY, 2025)
This study compares Bangladeshi MOOC-based learning institutions to examine  the current situation of online learning platforms in Bangladesh. Purposive sampling  in survey research was used to collect data from five institutions in Dhaka, including  government and commercial organizations. The purpose of the study was to investigate  the following topics: the reasons for providing online courses; the kinds of courses and  materials offered; the target audience; teaching strategies; learner activities; and the  difficulties faced by MOOC providers. A standardized questionnaire with a five-point  Likert scale was used to gather the data. Descriptive statistics were employed to analyze  the data. The results show various course offerings, emphasizing spoken language  instruction, admission and skill development courses, and curriculum support resources  for secondary schools. The primary target audience consists of adults and students, with  the institutions hoping to lower the cost of education, improve accessibility, and close  the gap between formal and informal education. In addition to exams and assignments,  the study lists web-based communication platforms, multimedia tools, and video  recordings as common instructional techniques. On the other hand, issues with learner motivation, restricted internet connection, real time engagement, and the quality of the course materials were also noted as common  challenges. Based on these results, the study suggests introducing interactive elements,  improving content accessibility and clarity, developing student engagement, and  overcoming communication gaps to customize learning materials to varied learner  requirements. This research adds to our understanding of the MOOC-based learning  environment that exists in Bangladesh today and offers insightful information for future  growth and development that will increase the overall efficacy of this teaching strategy.
Keywords: MOOCs; online learning; Bangladesh; teaching methods; educational resources; challenges